(untitled) (Wire Insights: Journal of Innovation Insights, 2024)
In modern industry, one of the primary goals is to increase the efficiency of production processes and improve product quality. Quantitative models and quality control tools play a significant role in the improvement of industrial processes. This article presents the theoretical foundations of qualitarian models and quality management tools, methods of their use and practical examples.